2014
DOI: 10.1007/s10068-014-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and anti-fungal effect of endo-β-1,3-glucanase from Thermotoga maritima

Abstract: A gene encoding an endo-β-1,3-glucanase from Thermotoga maritima MSB8 (TmβG) was cloned and expressed in Escherichia coli. The purified enzyme produced various β-1,3-glucooligosaccharides from soluble laminarin, and mainly β-1,3-glucooligosaccharides smaller than laminaritetrose from insoluble curdlan. The optimum pH and temperature of the enzyme were 5.0 and 80ºC, respectively. TmβG inhibited the growth of Candida albicans, which indicates that the enzyme could potentially be used as an anti-fungal agent to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…β-1,3-Glucanase displayed high tolerance towards DMSO, with >70% activity retained, while acetonitrile and acetone significantly decreased enzyme activity up to 50% (Figure 5). These results are concurrent with those of previous studies reporting that methanol, ethanol, and DMSO (all 10%) decreased the relative activity of Thermotoga maritima β-1,3-glucanase by 52%, 34% and 16%, respectively [35].…”
Section: Characterization Of β-13-glucanase From Y Lipolytica Transformant (Pylsc1-13g)supporting
confidence: 91%
“…β-1,3-Glucanase displayed high tolerance towards DMSO, with >70% activity retained, while acetonitrile and acetone significantly decreased enzyme activity up to 50% (Figure 5). These results are concurrent with those of previous studies reporting that methanol, ethanol, and DMSO (all 10%) decreased the relative activity of Thermotoga maritima β-1,3-glucanase by 52%, 34% and 16%, respectively [35].…”
Section: Characterization Of β-13-glucanase From Y Lipolytica Transformant (Pylsc1-13g)supporting
confidence: 91%
“…In particular, as a result of barley β-glucan hydrolises, Jermuk-LamM produces minimal glucose, while FLamA and FLamB generate glucose as one of the primary end products [89]. Thus, based on the biochemical characteristics, substrate specificity and product pattern we classify Jermuk-LamM as a typical endo-β-1,3-glucanase of the GH16_3 subfamily (EC 3.2.1.39) [90] together with TmβG from the bacterium Thermotoga maritima MSB8 [43] and LamA from the archaeon Pyrococcus furiosus , respectively [91].…”
Section: Discussionmentioning
confidence: 99%
“…Laminarinases have been characterised from plants [28], fungi [29,30,31,32], algae [33], Actinobacteria [34,35], Archaea [36], soil bacteria [37,38,39], thermophilic [40,36,41,42,43,44] and marine bacteria [45,46,47,21,48,49]. Most of the characterised laminarinases belong to glycosyl hydrolase family 16 (GHF16) [50].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the anti-fungal activity of rGluY against C. albicans was relatively stronger than those of other known functional homologs against the same fungal pathogen. Previously, S. matensis ATCC 23,935 GH64 endo-β-1,3-glucanase (SmβG) [8] and Thermotoga marimata endo-β-1,3-glucanase (TmβG) [34] were also reported to inhibit over…”
Section: Anti-fungal Activities Of Rgluy and Rgluyδricinmentioning
confidence: 99%
“…These results indi-cated that the anti-fungal activity of rGluY against C. albicans was relatively stronger than those of other known functional homologs against the same fungal pathogen. Previously, S. matensis ATCC 23,935 GH64 endo-β-1,3-glucanase (SmβG) [8] and Thermotoga marimata endo-β-1,3-glucanase (TmβG) [34] were also reported to inhibit over 60% of the growth of C. albicans at concentrations exceeding 0.1 mg/mL (approximately 2 µM) and 0.2 mg/mL (approximately 2.7 µM), respectively. Compared to rGluY, it was found that rGluY∆RICIN even at a concentration of 0.5 mg/mL (approximately 11.6 µM) could only inhibit 60% of the growth of C. albicans.…”
Section: Anti-fungal Activities Of Rgluy and Rgluy∆ricinmentioning
confidence: 99%